The assessment of comparative advantage of the non-ruminant subsector through policy analysis matrix (PAM) in Peninsular Malaysia - Abd Latif, Ismail; Md Isa, Abu Hassan; Zainal Abidin, Zuliana; Rezai, Golnaz; Sharifuddin, Juwaidah; Mohamed, Zainal Abidin (Universiti Putra Malaysia Press, 2015)
The objective of this study was to assess comparative advantages of the non-ruminant subsector in selected states of Peninsular Malaysia. The study analysed livestock production, namely chicken meat and eggs in three states i.e. Negeri Sembilan, Perak and Selangor. This study used a Policy Analysis Matrix (PAM) to determine whether non-ruminant products have a comparative advantage for production under commercial, medium or small scale farm size. The study demonstrated that Malaysia has a strong comparative advantage in the production of chicken meat compared to the production of eggs. Chicken meat produced on a commercial scale has a DRC ratio of 0.24 while eggs produced on a medium scale have a DRC ratio of 0.26. Both farms have a comparative advantage because their ratio implies that the value added per unit of product is larger than the value of domestic resources used to produce in that unit. According to Tsakok (1990), the level of comparative advantage of each subsector is greatest if the DRC ratio is close to zero. As a result, broiler farms on commercial scale with a DRC ratio of 0.24 have a higher degree of comparative advantage compared to layer farms on a commercial scale with DRC ratio of 0.71.